2022
DOI: 10.2106/jbjs.rvw.22.00133
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Abductor Tendon Tears

Abstract: Greater trochanteric pain syndrome consists of a group of associated conditions involving the lateral hip that can be debilitating to patients, mostly women between ages 40 and 60 years.» Abductor tendon tears are becoming a more recognized cause of lateral hip pain in patients without hip osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…While the exact incidence of hip abductor tendon tears in those presenting with symptomatic GTPS has not been reported to the best of our knowledge, their contribution is now acknowledged more widely and highlighted by the array of open, endoscopic and augmented surgical techniques now reported [ 2 , 7 , 11 , 13 , 15 , 16 , 18 , 22 , 23 ]. Published reviews have reported encouraging outcomes overall [ 1 , 4 , 8 , 19 21 , 26 , 39 ], with patient satisfaction rates ranging from 66 to 90%, [ 3 , 31 , 32 , 36 ] and similar clinical and functional outcomes in patients undergoing open and endoscopic hip abductor tendon repair methods [ 1 , 4 ]. However, a higher complication and re-tear rate has been reported with open (versus endoscopic) repair [ 1 , 26 ], with a review published by Alpaugh et al [ 1 ] reporting an overall surgical complication rate of 13% in those undergoing open repair (with a 9% re-tear rate), versus a complication rate of 3% in those undergoing endoscopic repair (with no re-tears).…”
Section: Introductionmentioning
confidence: 99%
“…While the exact incidence of hip abductor tendon tears in those presenting with symptomatic GTPS has not been reported to the best of our knowledge, their contribution is now acknowledged more widely and highlighted by the array of open, endoscopic and augmented surgical techniques now reported [ 2 , 7 , 11 , 13 , 15 , 16 , 18 , 22 , 23 ]. Published reviews have reported encouraging outcomes overall [ 1 , 4 , 8 , 19 21 , 26 , 39 ], with patient satisfaction rates ranging from 66 to 90%, [ 3 , 31 , 32 , 36 ] and similar clinical and functional outcomes in patients undergoing open and endoscopic hip abductor tendon repair methods [ 1 , 4 ]. However, a higher complication and re-tear rate has been reported with open (versus endoscopic) repair [ 1 , 26 ], with a review published by Alpaugh et al [ 1 ] reporting an overall surgical complication rate of 13% in those undergoing open repair (with a 9% re-tear rate), versus a complication rate of 3% in those undergoing endoscopic repair (with no re-tears).…”
Section: Introductionmentioning
confidence: 99%